2020
DOI: 10.3389/fimmu.2020.00724
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Cross-Talk With NLRP3 Inflammasome and Complement Signaling Pathways in Alzheimer's Disease

Abstract: Amyloid plaques, mainly composed of abnormally aggregated amyloid β-protein (Aβ) in the brain parenchyma, and neurofibrillary tangles (NFTs), consisting of hyperphosphorylated tau protein aggregates in neurons, are two pathological hallmarks of Alzheimer's disease (AD). Aβ fibrils and tau aggregates in the brain are closely associated with neuroinflammation and synapse loss, characterized by activated microglia and dystrophic neurites. Genome-wide genetic association studies revealed important roles of innate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(161 citation statements)
references
References 208 publications
(242 reference statements)
4
156
0
1
Order By: Relevance
“…The presence of the MAC demonstrates that complete activation of the cascade does occur within the AD brain and thus is evidence for the generation of C5a and C3a. While complement activation products C5a and C3a may bind to their receptors and recruit phagocytic cells to the plaque (the source of the generated C3a and C5a), the intracellular signaling of C5a (and C3a) on microglia is predicted to synergize with plaque fAβ ligation of the TLRs inducing a chronic inflammatory state mediated substantially by locally produced pro-inflammatory cytokines as well as other neurotoxic species (reviewed in [ 161 ]). Ablation of C1q in the transgenic hAPP Tg2576 mouse model supported such a scenario as the absence of C1q, and thus inability to generate the downstream classical complement pathway products C3a and C5a, resulted in significant and substantial decreases in microgliosis and astrocytosis and prevention of synaptophysin and MAP2 loss in the CA3 region of the hippocampus [ 91 ].…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the MAC demonstrates that complete activation of the cascade does occur within the AD brain and thus is evidence for the generation of C5a and C3a. While complement activation products C5a and C3a may bind to their receptors and recruit phagocytic cells to the plaque (the source of the generated C3a and C5a), the intracellular signaling of C5a (and C3a) on microglia is predicted to synergize with plaque fAβ ligation of the TLRs inducing a chronic inflammatory state mediated substantially by locally produced pro-inflammatory cytokines as well as other neurotoxic species (reviewed in [ 161 ]). Ablation of C1q in the transgenic hAPP Tg2576 mouse model supported such a scenario as the absence of C1q, and thus inability to generate the downstream classical complement pathway products C3a and C5a, resulted in significant and substantial decreases in microgliosis and astrocytosis and prevention of synaptophysin and MAP2 loss in the CA3 region of the hippocampus [ 91 ].…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…C5a was found to increase the release of IL-1β and IL-6 when added to Aβ-primed human monocytes in vitro [ 179 ] and C5aR1 antagonists have been found to reduce proinflammatory cytokines (IL-1β) in periodontal disease [ 180 ]. Thus, it is possible that in the CNS, as in the periphery, C5a via C5aR1 signaling synergizes with TLR/NFκB and the NLRP3 inflammasome activity to trigger potent detrimental inflammatory responses [ 161 ]. If so, it would add further value to the use of a C5aR1 antagonist in AD, avoiding the systematic suppression of NLRP3, which could lead to susceptibility to infection.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…0000 , Karikó et al, 2004 , Kramer-Hämmerle et al, 2005 , Kužnik et al, 2011 , Lafon et al, 0000 , Lau et al. 0000 , Lee et al, 2015a , Lee et al, 2015b , Li et al, 2020a , Li et al, 2020b , Lööv et al, 0000 , Luo et al, 0000 , Morgello, 2020 , Ojha et al, 0000 , Olejnik et al, 0000 , Paniz‐Mondolfi et al, 2020 , Potokar et al, 0000 , Rodríguez-Gómez et al, 0000 , Saura, 0000 , Serramía et al, 2016 , Sofroniew, 2015 , Solà et al, 2002 , Yang et al, 2020a , Yang et al, 2020b .…”
Section: Uncited Referencesunclassified
“…These findings were confirmed by Ou et al who found that increasing A. muciniphila resulted in a reduction in Aβ 40 and Aβ 42 levels in the cerebral cortex of AD model mice (APP/PS1), and improved learning and completion rates in maze tests [ 176 ]. A possible pathway could be via the involvement of TLR4 in AD as aggregated Aβ can bind TLR4 and subsequently activate microglia, resulting in increased cytokine production (reviewed by [ 177 ]). Furthermore, several studies by Ashrafian et al demonstrated that A. muciniphila OMVs have the ability to decrease TLR4, resulting in decreased inflammation [ 178 , 179 ].…”
Section: Human Microbiome Dysbiosis As a Source Of A Systemic Chromentioning
confidence: 99%